Guanosine triphosphate cyclohydrolase I deficiency: a rare cause of hyperphenylalaninemia - Coşkun, Turgay; Karagöz, Tevfik; Kalkanoğlu, Serap; Tokatlı, Ayşegül; Özalp, İmran; Thöny, Beat; Blau, Nenad (The Turkish Journal of Pediatrics, 1999)
Tetrahydrobiopterin (BH₄) deficiencies are a heterogeneous group of disorders caused by a defect in two of the three enzymes involved in its biosynthesis or in the two recycling enzymes. Except for the deficiency of dehydratase, an enzyme catalyzing a reaction in the recycling pathway, all other variants of BH₄ deficiency are characterized by developmental delay, progressive neurological deterioration, hypokinesis, drooling, swallowing difficulty, truncal hypotonia, increased limb tone, myoclonus and brisk deep tendon reflexes.A deficiency of guanosine triphosphate cyclohydrolase I (GTPCH), the first enzyme in the biosynthetic pathway of BH₄, is described in a 14-month-old male infant with hyperphenylalaninemia, developmental delay, hypertonia of the extremities, seizures, feeding difficulties, and vomiting. Urinary pteridine screening revealed very low levels of neopterin and biopterin which was highly suggestive of GTPCH deficiency. Low cerebrospinal fluid concentrations of 5-hydroxyindoleacetic acid (5HIAA) and homovanillic acid concentrations, together with no detectable neopterin and decreased concentrations of biopterin and folate, agreed with the diagnosis of GTPCH deficiency. Subsequently measured neopterin and biopterin synthesis in cytokine-stimulated skin fibroblasts confirmed GTPCH deficiency, albeit indirectly. The patient showed marked improvement on a low-protein low-phenylalanine diet with neurotransmitter precursor administration. The favorable outcome in this patient clearly shows that not only newborns with elevated phenylalanine levels but also older children with neurological signs and symptoms should be screened for a BH₄ deficiency in order to have maximum benefit of the treatment.
Keywords: hyperphenylalaninemia; guanosine triphosphate cyclohydrolase I deficiency; neopterin; biopterin; neurotransmitters; neonatal screening